Mammalian autophagy: core molecular machinery and signaling regulation - Yang, Zhifen (2009)
Autophagy, a cellular catabolic pathway, is evolutionarily conserved from yeast to mammals. Central to this process is the formation of autophagosomes, double-membrane vesicles responsible for delivering long-lived proteins and excess or damaged organelle into the lysosome for degradation and reuse of the resulting macromolecules. In addition to the hallmark discovery of core molecular machinery components involved in autophagosome formation, complex signaling cascades controlling autophagy have also begun to emerge, with mTOR as a central but far from exclusive player. Malfunction of autophagy has been linked to a wide range of human pathologies, including cancer, neurodegeneration and pathogen infection. Here we highlight recent advances in identifying and understanding the core molecular machinery and signaling pathways that are involved in mammalian autophagy.